2020
DOI: 10.31234/osf.io/dpgx5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does a blind person see? Developmental change in applying visual verbs to agents with disabilities

Abstract: Classic theories emphasize the primacy of first-person sensory experience for learning meanings of words: to know what “see” means, one must be able to use the eyes to perceive. Contrary to this idea, blind adults and children acquire normative meanings of “visual” verbs, e.g., interpreting “see” and “look” to mean with the eyes for sighted agents. Here we ask the flip side of this question: how easily do sighted children acquire the meanings of “visual” verbs as they apply to blind agents? We asked sighted 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the one hand, 3‐year‐old blind children understand the semantics of vision‐related words—such as look and see—in a manner comparable to their sighted peers (Elli et al., 2021; Landau & Gleitman, 1985). Studies on word comprehension also show no difference between blind and sighted people in semantic judgments of object concepts, actions, and vision‐related terms (Bedny et al., 2012, 2019; Kim et al., 2021; Mahon et al., 2009; Marmor, 1978; Saysani et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, 3‐year‐old blind children understand the semantics of vision‐related words—such as look and see—in a manner comparable to their sighted peers (Elli et al., 2021; Landau & Gleitman, 1985). Studies on word comprehension also show no difference between blind and sighted people in semantic judgments of object concepts, actions, and vision‐related terms (Bedny et al., 2012, 2019; Kim et al., 2021; Mahon et al., 2009; Marmor, 1978; Saysani et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…That is, see can report a belief one has about one thing (such as a book falling) as a result of perceiving of something else with entirely different visual properties (such as a book on the floor). Previous research has shown that young children (around age 4) do in fact have difficulty learning some aspects of perception verb semantics, and tend to assign narrower meanings to perception verbs than older children or adults, treating verbs like see as only reporting an event involving direct perception with one's eyes (Landau & Gleitman 1985, Elli, Bedny & Landau 2021.…”
mentioning
confidence: 99%